Efek Pemberian Ekstrak Kacang Tanah (Arachis hypogaea L.) Terhadap Kadar Gula Darah pada Mencit (Mus musculus L) - Ersalina Nidianti; Devyana Dyah Wulandari; Chika Nur Azizah (Universitas Borneo Lestari, 2023)
Diabetes mellitus is a group of metabolic-related diseases characterized by chronic hyperglycemia that occurs due to abnormalities in insulin secretion. The prevalence of diabetes is estimated to increase as the population ages from 111.2 million people aged 65-79 years. This figure is predicted to continue to increase to reach 578 million in 2030 and 700 million in 2045. The purpose of this study was to analyze the effect of giving peanut extract (Arachise hypogaea L) on blood sugar levels in mice (Mus musculus L). The research method is experimental, with a pre-post test only control group design. The samples used were mice blood. The results showed that the average blood sugar levels in the untreated group were (69.91 mg/dL), distilled water (189.60 mg/dL), peanut extract at a dose of 25% (156.93 mg). /dL), peanut extract 50% (88.25 mg/dL) and peanut extract 75% (80.07 mg/dL). The conclusion is that there is an effect of giving Peanut Extract (Arachis hypogaea L.) on Blood Sugar Levels in Mice (Mus musculus L).